P3-S1.34 Evaluation of the Roche cobas 4800 for the detection of Chlamydia trachomatis and Neisseria gonorrhoeae using endocervical specimens. (10th July 2011) - Pantone, A; Van Der Pol, B; Lillis, R; Loyd, B; Nye, M B; Taylor, S
Abstract : Background: The Roche cobas 4800 (cobas) is a new diagnostic assay that utilises an automated workstation to isolate nucleic acids from clinical specimens and a real time instrument for the detection of C trachomatis (CT) and N gonorrhoeae (NG). The objective of this study was to compare the performance characteristics of the cobas to the BD Viper (Viper) and GenProbe Aptima Combo 2 (AC2) assays for the detection of CT and NG using a patient infected standard (PIS). Methods: Specimens were obtained from women attending STD, family planning, or OB/GYN clinics from 12 geographically distinct locations. Endocervical swabs (ES) and samples in ThinPrep liquid based cytology medium (LBC) were obtained from each participant as were urine samples (data not shown) and vaginal swabs (data not shown). LBC were sampled prior to cytology (prequot) for cobas and AC2 and after cytology (postquot) for cobas only. A patient was considered infected if at least 2 of the assays with different molecular targets gave positive results from the ES or urine samples. Results: Overall CT sensitivity ranged from 89.7 to 92.8% and specificity ranged from 99.6 to 99.8% for all sample types. Overall GC sensitivity ranged from 95.6 to 97.1% and specificity from 99.9 to 100% see Abstract P3-S1.34 table 1 . Conclusions: The cobas assay has excellent sensitivity and specificity when compared to PIS. Equivalent performance was observed for the ES and LBC samples, providing clinicians with flexibility to tailor endocervical sample acquisition to their particular setting. There was no statistical difference between the pre- and post-quot LBC samples allowing specimen handling to be suited to the needs of the microbiology and cytology laboratories. The assay is easy to perform, automated, and can be completed in <4 h.